Cyber Power Balancing and the Militarization of Cyberspace: Rethinking Asymmetric Warfare in the Digital Age - Habibi Tri Tulodo; Muhammad Afifudin; Ari Pitoyo Sumarno (Cita konsultindo, 2026)
The rapid militarization of cyberspace has fundamentally reshaped the strategic logic of asymmetric warfare. While existing scholarship recognizes cyberspace as an operational domain, insufficient attention has been paid to how cyber capabilities structurally transform power asymmetry and deterrence dynamics in contemporary conflicts. This article examines the institutionalization of military cyber capabilities and analyzes their implications for the transformation of asymmetric warfare from a global strategic studies perspective. Using qualitative document analysis of military doctrines, policy reports, and contemporary conflict cases, the study argues that cyberspace functions not merely as a supplementary domain but as a structural equalizer that enables weaker actors to generate strategic effects against materially superior adversaries. The findings reveal the emergence of cyber power balancing, gray-zone coercion, and multi-domain integration as defining characteristics of modern asymmetric conflict. The article proposes a conceptual framework linking cyber militarization, strategic asymmetry, and evolving deterrence logics. It concludes that cyberspace has become a central arena of persistent strategic competition, necessitating adaptive governance mechanisms and doctrinal innovation.